Why do Borrowers Become Over-Indebted? The Roles of Financial Literacy, Risk Perception, and Behavioral Bias in Peer-to-Peer Lending - Evi Grediani; Tio Waskito Erdi (Universitas Hayam Wuruk Perbanas, 2026)
The increasing use of online lending among young adults has raised concerns regarding over-indebtedness. This study aims to examine the effects of financial literacy, risk perception, and behavioral bias on over-indebtedness in online loan users, with financial self-control as a moderating variable. This research employs a quantitative approach using primary data collected through questionnaires from online lending users aged 20–29 years with moderate income levels. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that financial literacy, risk perception, and behavioral bias have a positive and significant effect on over-indebtedness. Behavioral bias is identified as the most dominant factor influencing excessive debt behavior. Furthermore, financial self-control weakens the effect of financial literacy on over-indebtedness, strengthens the effect of risk perception, but does not significantly moderate the relationship between behavioral bias and over-indebtedness. The findings indicate that rational factors such as knowledge and risk awareness are insufficient to prevent over-indebtedness without effective self-control mechanisms. This study contributes to behavioral accounting literature by highlighting the critical role of psychological and self-control factors in explaining digital debt behavior among young adults.